Technical and tactical aspects of two- handed backhand blocked return in the singles men - Teusdea, C. (Science, Movement & Health, 2018)
Problem statement. In the past, the two- handed backhand blocked return was considered a blow to putting the ball into play. With the upgrading of serve one, the increase in execution speed at this blow also aroused the problem of the high difficulty of the two- handed backhand blocked return. If on a quick surface, serve one can decide the fate of a match, so the two- handed backhand blocked return, if well executed, can change the fate of the match, becoming an important weapon for victory. As most players serve the opponent's lapel as the weaker hit, it is necessary to know some technical and tactical aspects of the execution of this technical element. The aim of the research. In actual tennis by using the two- handed backhand blocked return can earn points in the game if executed efficiently in technically and tactically. Knowing the technical and tactical aspects of the two- handed backhand serve return is important in the process of learning and development especially in the children. The two- handed backhand blocked return is a blow base and play an essential role in learning the game of tennis. Conclusions. The two- handed backhand blocked return is executed on hard first serve with two hands in three successive sequences and various processes. The serve and the return are part of the first phase when disputing the point in a single game. The tactical and success of the return is determined by certain factors, by content of the serve and the subsequent actions of the servant. The men's single is a game between two players or two teams of players who send the ball over a net with the help of the rackets, takes place after a certain game structure and a simple field with specific dimensions.